Effects of ozone and GAC on the removal of acetylsalicylic acid - Oussama Khemis; Gabriel Racovițeanu; Elena Vulpașu (E3S Web of Conferences)
The presence of pharmaceutical micropollutants from different families in water has become a serious environmental and human health problem. The treatment processes used to eliminate pharmaceutical pollutants are limited, and only some areeffective in removing certain pharmaceutical substances. Our study focused on reducing the pharmaceutical substance acetylsalicylic acid intended for human consumption at various concentrations (1.6 mg/l, 0.8 mg/l, and 0.4 mg/l organic matter (TOC)). The study was developed on two treatment processes (ozonation process (O3) and adsorption process with granular actif carbon) and two different flow rates (1.25 l/min with an EBCTof 6 min, 2.5 l/min with an EBCT of 3 min) applied in a large-scale drinking water treatment pilot. The O3/AC process obtained good results at a flow rate of 1.25 l/min (EBCT of 6 min) with total elimination at a concentration of 0.4 mg/L and 98.73% and 99.96% for higher concentrations of 1.6 mg/l and 0.8 mg/l respectively, which means that this processis capable of degrading and removing the pharmaceutical substance acetylsalicylic acid.